Nef stimulates human immunodeficiency virus type 1 proviral DNA synthesis. - Aiken, C (1995)
The Nef protein of human immunodeficiency virus type 1 (HIV-1) stimulates viral infectivity. The mechanism of this phenotype was investigated. Viruses containing disrupted nef genes were 4 to 40 times less infectious than wild-type HIV-1 in a single-round infection. The Nef-mediated stimulation HIV-1 infectivity was dependent on the association of Nef with the plasma membrane and could be observed when Nef was provided in trans in the virus producer but not target cells. The impaired infectiousness of nef-defective (delta Nef) virions was observed whether or not CD4 was present in either of these cells. Furthermore, it was independent of the mode of viral entry, since it was not rescued by pseudotyping Env- HIV-1 virions with the amphotropic murine leukemia virus envelope glycoproteins. As predicted from this result, wild-type and delta Nef virions entered cells with equal efficiencies. However, despite their normal content in viral genomic RNA and reverse transcriptase activity, delta Nef viruses were limited in their ability to perform reverse transcription once internalized in several cell types, including peripheral blood lymphocytes. Since Nef does not appear to be abundant in virions, these results suggest that Nef acts in producer cells to allow the generation of particles fully competent for completing steps that follow entry, leading to efficient reverse transcription of the HIV-1 genome. Using a trans complementation assay, we found that Nef proteins from a number of primary HIV-1 isolates as well as, to a milder degree, those from HIV-2ST and SIVMAC239 could enhance the infectivity of delta Nef HIV-1. This indicates that the Nef-mediated stimulation of proviral DNA synthesis is highly conserved and likely plays an important role in vivo.